Influence of different treatments of the ceramic surface and thermal cycling on the bond strength of brackets to ceramic - SÁEZ,Fernando Guerra (2017)
Abstract Objective To evaluate in vitro the effect of different treatments of the ceramic surface and thermal cycling on the shear bond strength (SBS) of metallic brackets bonded to feldspathic ceramic. Material and method Ceramic cylinders were divided into four groups (n=4) according to the treatment of ceramic surface: G1-Clearfil Ceramic Primer silane and Transbond XT (CCPT); G2-etched with 10% hydrofluoric acid (HFA) for 60 s, CCP and Transbond XT (ACCPT); G3-etched with 10% HFA for 60 s, Ambar Adhesive and Transbond XT (AAAT); and, G4 - etched with 10% HFA for 60 s, RelyX Ceramic Primer silane -RCP, adhesive primer Transbond and Transbond XT (ACPPT). Brackets were bonded to the cylinders with Transbond XT and light-activated for 40 s with LED Radii Plus. All specimens were stored in deionized water at 37 °C for 24 h, and two cylinders from each group were subject to 7,000 thermal cycles in a thermal cycler (5 °C/55 °C). After storage and thermal cycling, the SBS test was performed at a crosshead speed of 1 mm/min. Data were subjected to two-way ANOVA and Tukey’s post hoc test (α=0.05). Result The SBS of ACCPT was significantly higher than the other groups (p<0.05). The specimens submitted to thermal cycling showed significantly lower SBS than those without thermal cycling (p<0.05), regardless the ceramic surface treatment. The ARI showed predominance of score 0 for all groups. Conclusion Acid etching, CCP silane and Transbond XT method obtained the best results for bracket bonding. Thermal cycling reduced SBS for all groups. Score 0 was predominant for ARI in all groups.